Clinical Supervision, Learning Management, and Information Technology on Teacher Performance - Junaidi; Mattalatta; Malik, Tajuddin (Cendekiawan Indonesia Timur, 2023)
Learning innovations in schools occur in the school system, which includes existing components. Among them is the school education system, which consists of curriculum, rules, and organizational management of learning resource centers. Teacher performance can be seen and measured based on the specifications or competency criteria that every teacher must have. This research is included in the category of literature research, namely first, by noting all findings regarding consumption motivation in general in each research discussion obtained in the literature and sources. In the era of digital technology disruption, the idea of learning facilitated by teachers is more related to digital technology because most students are more interested in paying attention to the essential things, so information and communication technology-based learning is needed to support the professionalism of a teacher. The performance of clinical supervision is for the improvement and development of the teaching and learning process in total, such as improving the quality of teacher teaching, fostering the growth of the teaching profession in a broad sense, including the provision of facilities that support the smooth teaching and learning process, improving the quality of teacher knowledge and skills, providing guidance and coaching.